The container loading problem with cargo stability: a study on support factors, mechanical equilibrium and grids. Issue 7 (3rd July 2021) - Oliveira, Liliane de Azevedo; de Lima, Vinícius Loti; de Queiroz, Thiago Alves; Miyazawa, Flávio Keidi
Abstract : Approaches based on mechanical equilibrium are described for handling cargo stability in the container loading problem. This problem is expressed as an integer programming model and solved with a branch-and-cut algorithm. Cutting planes are added to avoid generating unstable packings. Three grids of points are used to pack items, and then their weakness and advantages, when combined with the cargo stability, are discussed. Computational results on 180 instances from the literature show that the support factor underestimates the solution, as the proposed approaches allowed stable packings with a higher volume.